2005
DOI: 10.1007/s00249-005-0487-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regions underlying the activation of low- and high-voltage activating calcium channels

Abstract: We have studied two aspects of calcium channel activation. First, we investigated the molecular regions that are important in determining differences in activation between low- and high-voltage activated channels. For this, we made chimeras between the low-voltage activating Ca(V)3.1 channel and the high-voltage activating Ca(V)1.2 channel. Chimeras were expressed in oocytes, and calcium channel currents recorded by voltage clamp. For domain I, we found that the molecular region that is important in determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…In our previous work, we started to investigate this issue by creating S4-replacement chimeras between Cav3.1 (α 1 G) channel (lowvoltage-activating and fast voltage-dependent inactivation) and Cav1.2 (α 1 C) (high-voltage-activating and little voltage-dependent inactivation) and also by using cysteine-scanning mutagenesis techniques. Our data showed that the S4 segments moved outward upon Cav3.1 channel depolarization, but surprisingly S4s did not account for the difference in voltage-dependent activation between Cav3.1 and Cav1.2 channels [7,8] .…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In our previous work, we started to investigate this issue by creating S4-replacement chimeras between Cav3.1 (α 1 G) channel (lowvoltage-activating and fast voltage-dependent inactivation) and Cav1.2 (α 1 C) (high-voltage-activating and little voltage-dependent inactivation) and also by using cysteine-scanning mutagenesis techniques. Our data showed that the S4 segments moved outward upon Cav3.1 channel depolarization, but surprisingly S4s did not account for the difference in voltage-dependent activation between Cav3.1 and Cav1.2 channels [7,8] .…”
mentioning
confidence: 51%
“…Spaetgens and Zamponi [9] , Talavera et al [15] and Park et al [16] showed that multiple structural elements contributed to the inactivation process of calcium channels, suggesting a global conformation change in the channel protein during inactivation. Our previous data showed that S4s in Cav3.1 moved outward during membrane depolarization [8] . In the present study, we found that S4 in domain I was involved in the voltage-dependence of inactivation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first letter represents the amino acid, the next number indicates the domain or repeat number, the second letter represents the segment type [e.g., p, pore; o, transmembrane segment 5; i, transmembrane segment 6], the final number indicates the relative number of the residue in the segment), and the attached phenyl group shows faceto-face interaction with the aromatic rings of Y3i10 and Y4i11. Furthermore, a recent chimera experiment between L-type and T-type Ca 2+ channels indicated that differences in the activation voltage range are due to the amino acid sequence of the S5-P-S6 region of domain 1 and 2 (Guda et al, 2007), although the S4 segment is regarded as the voltage-sensing and regulating voltage-gating segment of the Ca 2+ channel (Li et al, 2005). These results suggest that F2i11 may make similar interactions with BMS as Y3i10 and Y4i11.…”
Section: Discussionmentioning
confidence: 93%
“…However, exchange of only the S4 segments did not provide evidence of active contribution to the difference in voltage dependent activation of these channel families [8]. Detailed studies on domain I by the same group pointed out its importance for channel activation and showed that the S5 and S6 region rather than voltage sensing S1-S4 were critical [9]. Swapping of S4 segments between Cav3.3 channels and Ca V 1.2 channels demonstrated that IIS4 and, to a lesser degree IVS4, segments are crucial in determining the negative voltage threshold of Ca V 3.3 channel activation [10].…”
Section: Introductionmentioning
confidence: 99%